Rainfall forecasts, weather and wages over the agricultural production cycle - Mark R. Rosenzweig; Christopher Udry (Yale University, Economic Growth Center, 2014)
We look at the effects of rainfall forecasts and realized rainfall on equilibrium agricultural wages over the course of the agricultural production cycle. We show theoretically that a forecast of good weather can lower wages in the planting stage, by lowering ex ante out-migration, and can exacerbate the negative impact of adverse weather on harvest-stage wages. Using Indian household panel data describing early-season migration and district-level planting- and harveststage wages over the period 2005-2010, we find results consistent with the model, indicating that rainfall forecasts improve labor allocations on average but exacerbate wage volatility because they are imperfect.
Keywords: O12; O13; O15; Q12; J2; 330; wages; forecasting; migration; Niederschlag; Prognose; Agrarberufe; Lohn; Volatilität; Agrarproduktion; Produktlebenszyklus; Indien